Energy, exergy and exergoeconomic (3E) analyses and multi-objective optimization of a solar and geothermal based integrated energy system - Behzadi, Amirmohammad; Gholamian, Ehsan; Ahmadi, Pouria; Habibollahzade, Ali; Ashjaee, Mehdi (Applied thermal engineering, 2018)
•An integrated energy system with geothermal power plant, a PVT and a double-effect absorption chiller is proposed.•Comprehensive Thermodynamic and exergoeconomic analysis is carried out and a multi-objective optimization is done.•The optimized value of the overall exergy efficiency and the total product unit cost found to be 12.31% and 35$/GJ.•The condenser of geothermal system is the major source of irreversibility with the exergy destruction of 32.95 kW. A complete renewable energy source based on a solar and a geothermal system is proposed to produce desired electricity and cooling. The proposed system consists of a concentrated PVT, a double-effect LiBr-H2O absorption chiller and a geothermal unit. To better understand the system performance, energy, exergy and exergoeconomic analyses are investigated. The results show that recovering the waste heat of the geothermal unit increases the coefficient operation factor by about 15%. Second law analysis exhibits that one of the main parts of irreversibility occurs in the PVT with 29.6  kW. Results of exergoeconomic analysis show that in the second condenser and the cooling set, the exergy destruction cost has major effect on the component cost rate. In addition, the parametric study of major parameters (i.e., geothermal temperature, high pressure and low pressure turbine inlet pressure, PVT module’s temperature and area) is performed thermodynamically and thermoeconomically. In addition, by considering the overall exergy efficiency and the total product unit cost as objective functions, a multi-objective optimization is implemented based on genetic algorithm. From the Pareto frontier diagram, the value of an optimal point for single and multi-objective optimization are determined. Obtained results show that at the optimal point where the overall exergy efficiency and total product unit cost are optimized, the corresponding values are 12.31% and 35  $/GJ, respectively. Scattered distribution of the major parameters reveals that the geothermal temperature is a very sensitive parameter which should be kept at its highest value (i.e., 245 °C).